Características e conhecimentos sobre tabagismo em grupos específicos: adolescentes e gestantes - Bertani, André Luís [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Identify the characteristics and knowledge related to adolescents tabagism and the electronic media most used by this group. Exploratory study with interviews were done with 60 adolescents, smokers, ex-smokers or none smokers through specific interview approach with issues related to tabagism. In addition to questionnaire, the intensity of dependence was assessed through Fagerström test, motivation stages through Prochaska and DeClemente model and the suggested anxiety and depression symptoms by the hospital anxiety and depression scale of Zigmond & Snaith. The adolescent average age was 15,8 ± 1,1 years, 65% were female, 41,7% active smokers (60% girls) and 28,3% ex-smokers. The adolescents used to be in high school with 46,7% during their first year. Most of the adolescent smokers and ex-smokers (73,8%) started tabagism with ages between 14 and 16 years and 26,2 % between 10 and 13 years. Hookah smoking is popular between the adolescents to the extent that 81% of the smokers and ex-smokers had some experience with this form of tobacco consumption from tasting to current use. Between adolescents that believe that people start to smoke to show off with relation to cigarette 75% were smokers and between that believe that people start to smoke to parental influence 83,3% were smoker. The cardiac negative effect were identified by just 5% the kids and, in addiction, considerable proportion (20%) connect tabagism with some “benefits”. The internet through computers (58,3%) is an electronic media more used to have fun by the kids. The knowledge of adolescents on tabagism, non conventional way of tobacco and nicotine chemical dependence are not standardized or complete and, sometimes controversial. With respect to the result of this trial, is necessary to develop content coverage that by pass the errors of the knowledge on adolescents about tabagism, using internet tool as preference

Identificar as características e os conhecimentos relacionados ao tabagismo de adolescentes e as mídias eletrônicas mais utilizadas por este grupo. Estudo de característica exploratória onde foram realizadas entrevistas com 60 adolescentes, fumantes, ex-fumantes ou não-fumantes por meio de protocolo de entrevista específico com questões relacionadas ao tabagismo. Além do questionário, a intensidade da dependência foi avaliada por meio do teste de Fagerström, as fases de motivação pelo modelo de Prochaska e DiClemente e os sintomas sugestivos de ansiedade e depressão pela Escala Hospitalar de Ansiedade e Depressão de Zigmond e Snaith. A idade média dos adolescentes era de 15,8 ± 1,1 anos, 65% eram do sexo feminino, 41,7% fumantes ativos (60% meninas) e 28,3% ex-fumantes. Os adolescentes freqüentavam o ensino médio com 46,7% no primeiro ano. A maioria (73,8%) dos adolescentes fumantes e ex-fumantes iniciou o tabagismo com idades entre 14 e 16 anos e 26,2% entre 10 e 13 anos. O narguilé é popular entre os adolescentes tanto que 81% dos fumantes e ex-fumantes tiveram alguma experiência com esta forma de consumo do tabaco, desde a experimentação até o uso corrente. Entre os adolescentes que acreditavam que as pessoas começam a fumar por prestígio relacionado ao cigarro, 75% eram fumantes e daqueles que relataram que começam a fumar por influência dos pais e parentes, 83,3% eram fumantes. Os malefícios cardiovasculares foram identificados por apenas 5% dos adolescentes e, além disso, proporção considerável (20%) associa o tabagismo a algum “benefício”. A internet pelo computador (58,3%) é a mídia eletrônica mais utilizada para se divertir pelos adolescentes. Os conhecimentos dos adolescentes sobre tabagismo, sobre o uso de formas alternativas de tabaco e sobre dependência química da nicotina não são uniformes ou completos e, algumas vezes, equivocados. De acordo com os resultados deste estudo, é ...
Keywords: Mulheres grávidas; Adolescentes; Fumo - Vício - Tratamento; Mídia digital; Tobacco habit Treatment